Quality Changes of Dumbo Catfish (Clarias gariepinus) by Killing Techniques During Chilling Temperature Storage - Mala Nurilmala; . Nurjanah; Rahadian Hardja Utama (Jurnal Pengolahan Hasil Perikanan Indonesia, 2009)
The time of prerigor, rigor mortis, initial postrigor, and the end postrigor phase of catfish killed instantly in 0, 9, 57, and 144 hours was investigated. In addition, the time of prerigor, rigor mortis, initial postrigor, and the end of postrigor phase of catfish killed after 12 hours without water media were 0, 6, 42, and 120 hours. Freshness declination of catfish killed instantly slower than killed after 12 hours without water media. Fish killed instantly had 5.1x105 colonies/g TPC (Total Plate Count) value and 24.36 mg N/100 TVB (Total Volatile Base) value. The sensory value for eyes, gills, mucus of body surface, meats, odor, and texture at the end of storage (the sixth day) was 3.95, 4.05, 4.30, 4.45, 4.45 and 3.45 respectively. On the other hand the fish killed after 12 hours without water media had 1,2x106 colonies /g, TPC value and 25,2 mg N/100 g TVB value. The sensory value for eyes, gills, mucus of body surface, meats, odor, and texture at the end of storage (the sixth day) was 2.3, 2.2, 2.8, 3.9, 3.7 and 2.85, respectively.Keywords: catfish, fish quality, low temperature